Perancangan Pengamanan Akun dengan Menggunakan Mac Address pada Metode Enkripsi DES - Tambunan, Marihot Tora; Sulistyo, Wiwin (STMIK Palangkaraya, 2018)
Account security becomes very important as rapid development of internet and access. The case that was reported by Liputan6 about username and password stealing done by a hacker proves that sniffing exists in reality. One of encryption method, which can be used to secure an account’s user id and password, is DES. However, this algorithm is not always considered secure. Because of that, the researcher used mac address score for the authentication step during the log in process. It is done to cover flaw since DES encryption has been prone to be broken. The result of the examination shows that mac address is possible to be used during the authentication step. This model is also efficient to be used because the response duration is quiet quick, which is less than a second, even though the first trial would take some time and process to enter the system. This model can be used as server identifier to enable user to get login access by checking mac that has been exist in the user’s device.